Efecto anti-fúngico de compuestos bioactivos sobre Moniliophthora Roreri, agente causal de moniliasis en mazorcas de cacao - Salinas Malo, Jean Carlos (Machala : Universidad Técnica de Machala, 2024)
The study evaluated bioactive compounds to control Moniliasis in cocoa crops caused by the fungus Moniliophthora roreri. It was carried out in the plant health laboratory of the Technical University of Machala. The experiment used a non-parametric DCA with thirteen treatments replicated five times, totaling sixty-five experimental units. In the first phase, PDA culture medium was prepared for fungal inoculation. The initial phase of the experiment included the obtaining and processing of the plant material (Garlic, Ají gallinazo, Orégano, Ají rocoto) to prepare the hydroalcoholic extracts (EHA). The second phase involved inoculation and in vitro identification of the fungus and the evaluation of its activity against EHA. The final phase included a disease severity test. The data obtained were analyzed using the Kruskal-Wallis test due to the null normality and homogeneity of the variance in the data. In the first variable, the Treatments (T1,T2, T3, T4, T5, T6) there was no mycelial growth, therefore, they are the ones with the best results. For the second variable, the percentage of external damage to the cob was evaluated taking into account It counts the best results obtained in the first variable, giving satisfactory results in treatment T1. In conclusion, the EHA of garlic and oregano exhibited null results in the mycelial growth of the phytopathogenic fungus from the minimum concentration, compared to other treatments. These observations indicate promising potential as natural antifungal agents
El estudio evaluó compuestos bioactivos para controlar la Moniliasis en cultivos de cacao causada por el hongo Moniliophthora roreri. Se realizó en el laboratorio de sanidad vegetal de la Universidad Técnica de Machala. EL experimento utilizo un DCA no paramétrico con trece tratamientos replicados cinco veces, totalizando sesenta y cinco unidades experimentales. En la primera fase, se preparó medio de cultivo PDA para la inoculación del hongo. La fase inicial del experimento incluyó la obtención y procesamiento del material vegetal (Ajo, Ají gallinazo, Orégano, Ají rocoto) para elaborar los extractos hidroalcohólicos (EHA). La segunda fase involucró la inoculación e identificación in vitro del hongo y la evaluación de su actividad frente a los EHA. La fase final incluyó una prueba de severidad de la enfermedad. Los datos obtenidos fueron analizados mediante la prueba de Kruskal-Wallis debido a la nula normalidad y homogeneidad de la varianza en los datos. En la primera variable los Tratamientos (T1, T2, T3, T4, T5, T6) existió un nulo crecimiento micelial, por ende, son los de mejor resultado, para la segunda variable se evaluó el porcentaje de daño externo de la mazorca tomando en cuenta los mejores resultados obtenidos en la primera variable, dando resultados satisfactorios en el tratamiento T1. En conclusión, los EHA de ajo y orégano exhibieron resultados nulos en el crecimiento micelial del hongo fitopatógeno a partir de la mínima concentración, a comparación con otros tratamientos. Estas observaciones indican un prometedor potencial en calidad de agentes antifúngicos naturales.
Keywords: MONILIOPHTHORA RORERI; CRECIMIENTO MICELICIAL; COMPUESTOS BIOACTIVOS